The Florida Bull Test 2010-2011 - G. Cliff Lamb; Nicolas DiLorenzo (EDIS)
The North Florida Research and Education Center in Marianna, Florida annually hosts the Florida Bull Test. By controlling environmental factors and taking Expected Progeny Differences (EPD’s) into account, the data emphasizes the dual importance of genetics and environment in all cattle types. Beef cattle producers can use this information to select superior cattle for the best possible herd. This 5-page fact sheet provides the results of the 2010-11 Florida bull test. Written by G. Cliff Lamb and Nicolas DiLorenzo, and published by the UF Department of Animal Science, November 2011. (UF/IFAS photo by Thomas Wright)